A composite electrolyte with Na3Zr2Si2PO12 microtube for solid-state sodium-metal batteries. Issue 8 (15th April 2021) - Yu, Wenhao; Zhai, Yanfang; Yang, Guanming; Yao, Jianyao; Song, Shufeng; Li, Shuai; Tang, Weiping; Hu, Ning; Lu, Li
Abstract: Under considerations of material abundance, cost, redox potential, higher performance, and safety, solid-state sodium-metal batteries hold much promise. The development of solid electrolytes with superior electrical performances for the solid-state sodium batteries is at the infant stage and still remains a challenge. Herein, we for the first time report a synthetic strategy of Na3 Zr2 Si2 PO12 ceramic microtubes via a sol gel process with natural cotton fiber template. Moreover, an inorganic-organic composite electrolyte Na3 Zr2 Si2 PO12 microtube/poly (ethylene oxide) (PEO)-poly (vinylidene fluoride- co -hexafluoropropylene) (PVdF-HFP)-sodium perchlorate (NaClO4 )-1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EmimFSI) is developed. The phase, microstructure, and electrochemical properties of the Na3 Zr2 Si2 PO12 microtubes and their composite electrolytes are systematically investigated based on X-ray diffraction, scanning electron microscope, energy dispersive spectroscopy, electrochemical impedance spectroscopy, linear sweep voltammetry, direct-current polarization, and galvanostatic cycling. The finding implies that the characteristic Na3 Zr2 Si2 PO12 microtubes and their composite electrolytes are promising for solid-state sodium-metal batteries.